Shiva Temple from the Arthuna group of temples - Temples of India Project Team (Jio Institute, 2024)
This is the south-facing elevation of the Shiva Temple from the Arthuna group of temples. According to its plan, the temple consists of a mukhamandapa (front porch), a mandapa (pillared hall), an antarala (vestibule or antechamber) and a garbhagriha (sanctum sanctorum). Above the garbhagriha rises a lofty shekhari (multi-spire) shikhara. This is the only temple that has its shikhara in its complete form, albeit renovated. The temple structure on the exteriors has undergone several restorations. Many fallen architectural elements have been reassembled.